Bandgap Correction and Spin-Orbit Coupling Induced Absorption Spectra of Dimethylammonium Lead Iodide for Solar Cell Absorber - Agbaoye, Ridwan O.; Bolarinwa, Sherifdeen; Akiode, Kolawole Olubunmi; Adekoya-Olowofela, Abibat A.; Habeeb, Lateefat Modupe; Balogun, Omolola Myriam; Adebambo, Paul O.; Kenmoe, Stephane; Adebayo, Gboyega A. (Frontiers in Energy Research, 2021)
The search for stable and highly efficient solar cell absorbers has revealed interesting materials; however, the ideal solar cell absorber is yet to be discovered. This research aims to explore the potentials of DimethylammoniumLeadIodide (CH3NH2CH3PbI3) as an efficient solar cell absorber. (CH3NH2CH3PbI3) was modelled from the ideal organic-inorganic Perovskite cubic crystal struc- ture and optimized to its ground state. Considering the spin-orbit coupling (SOC) effects on heavy metals, the electronic band structure and bandgaps were calculated using the Density Functional Theory (DFT). In contrast, bandgap correction was achieved by using the GW quasiparticle meth- ods of the Many-body perturbation theory. The optical absorption spectra were calculated from the real and imaginary dielectric tensors, which is determined by solving the Bethe-Salpeter equations of the Many-Body Perturbation Theory. Spin-orbit coupling induces band splitting and bandgap reduction in both DFT and GW methods, while the GW method improves the DFT bandgap. We report a DFT band gap of 1.55 eV, while the effect of spin-orbit coupling reduces the bandgap to 0.50 eV. Similarly, the self-consistent GW quasiparticle method recorded a bandgap of 2.27 eV, while the effect of spin-orbit coupling on the self-consistent GW quasiparticle method reported a bandgap of 1.20 eV. The projected density of state results reveals that the (CH3NH2CH3PbI3) does not par- ticipate in bands around the gap, with iodine (I) p orbital and the lead (Pb) p orbital showing most prominence in the valence band and the conduction band. The absorption coefficient reaches 106 in the ultraviolet, visible, and near-infrared region, which is higher than the absorption coefficient of CH3NH3PbI3. The spectroscopic limited maximum efficiency predicts a high maximum efficiency of about 62% at room temperature and absorber thickness of about 10−1 to 102 micrometre, suggesting that (CH3NH2CH3PbI3) has an outstanding prospect as a solar cell absorber.